Microwave assisted ring-opening polymerization of Ɛ-caprolactone using organic acids - (:unkn) unknown (My University, 2023)
Microwave-assisted ring opening polymerization (ROP) of ε-caprolactone was performed using three different carboxylic acids as initiators. In order to determine the effect of the acidity strength of the initiators on the molecular weight and terminal group functionality, the acids from strongest to weakest, i.e. trifluoro acetic acid, acetic acid, and benzoic acid, were used as initiators. The microwave power was kept at 600 W. The chemical structure and thermal properties of the synthesized low molecular weight PCLs were determined using Fourier Transform Infrared Spectroscopy (FTIR), 1H Nuclear magnetic resonance (1H-NMR) spectroscopy, and differential scanning calorimetry (DSC). The molecular weight of the products was determined and compared using Light Scattering-Gel Permeation Chromatography (LS-GPC) and 1H-NMR spectroscopy. Their spectroscopic analyses showed that microwave-assisted polymerization is a useful technique in synthesizing the low molecular weight PCL without undesirable impurities. Melting points of the synthesized low molecular weight PCLs ranged from 52 °C to 63 °C, as determined by DSC. Their number-average molecular weights (Mn) and polydispersity index (PDI) were between 1.256—1.540 and 1.35—4.90 kDa, respectively. The Mn values obtained from the GPC were consistent with those calculated from 1H-NMR and matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF) techniques. These findings highlighted the significance of the microwave technique in obtaining low molecular weight PCL for drug delivery formulations.
Keywords: Kimya; Biyokimya; Biyoinorganik Kimya; Fizikokimya; Polimer Karakterizasyonu; Temel Bilimler; Mühendislik ve Teknoloji; Chemistry; Biochemistry; Bioinorganic Chemistry; Physical Chemistry; Characterization of Polymers; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Malzeme Bilimi; POLİMER BİLİMİ; KİMYA, ORGANİK; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); MATERIALS SCIENCE; CHEMISTRY; POLYMER SCIENCE; CHEMISTRY, ORGANIC; MATERIALS SCIENCE, MULTIDISCIPLINARY; Polimerler ve Plastikler; Fizik Bilimleri; Organik Kimya; Malzeme Kimyası; Polymers and Plastics; Physical Sciences; Organic Chemistry; Materials Chemistry; Acetic acid; Benzoic acid; Microwave; PCL; Poly epsilon-caprolactone; Ring-opening polymerization; ROP; Trifluoroacetic acid